(untitled) (Journal of Kathmandu Medical College, 2022)
Background: The maxillary labial frenum is frequently inserted in the mucogingival junction. However, it may show variation in attachment. Despite the fact that an aberrant labial frenum has been associated to a range of syndromic and non-syndromic disorders, it is frequently overlooked during routine intraoral examinations. Objectives: To find the prevalence of types of maxillary labial frenum attachment in patients visiting tertiary hospital in Nepal. Methods: This analytical cross-sectional study comprised of 140 patients visiting the dental outpatient department of Tribhuvan University Teaching Hospital from December 23, 2021 to March 13, 2022. Investigators assessed the patient’s frenum insertion in the dental chair with the lip softly pulled away from the alveolar process in a nearly horizontal direction under good lighting. Data were entered and analysed statistically using SPSS.v21 where mean, standard deviation, frequency, and percentage were calculated depending upon the nature of data. Fisher’s exact test was done to determine the association of age category and sex with the types of frenulum attachment. Results: Most of the individuals (83, 59.3%) had the mucosal type of frenum followed by gingival (46, 32.9%), papillary (9, 6.4%), and least with papillary penetrating (2, 1.4%). Age and sex did not show any association with types of frenulum attachment. Conclusion: The insertion level of the labial frenum may vary, implying the significance of careful assessment during an intraoral examination. It also suggests that in presence of the abnormal attachment, an effective treatment approach planned timely could prevent gingival and interdental papilla pathological alterations.